PENGARUH FINANCIAL STABILITY, FINANCIAL TARGET DAN EXTERNAL PRESSURE TERHADAP FINANCIAL STATEMENT FRAUD - Dayu, Dea; -, Efrinal (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2024)
The research is aimed at finding out the influence of Financial Stability, Financial Target and External Pressure on Financial Statement Fraud. The research was conducted at manufacturing companies on the IDX for the 2019 - 2023 period. The sample size for this research was 30 companies using the purposive sampling method. The hypothesis was tested using multiple regression analysis. The results of this research show that Financial Stability has a negative and significant effect on Financial Statement Fraud, Financial Target has a negative and significant effect on Financial Statement Fraud, External Pressure has a positive and significant effect on Financial Statement Fraud.